The Effectiveness Of Using Teaching Modules In The Independent Curriculum In Elementary Schools - Kadek Hengki Primayana (STAHN Mpu Kuturan Singaraja, 2022)
Teaching modules are often the subject of discussion by teachers at all levels, both elementary, middle and high levels. Basically, teaching modules are learning materials that are arranged extensively and systematically with reference to learning principles that are applied by teachers to students. Systematic can be interpreted sequentially starting from the opening, content of the material, and closing, making it easier for students to learn and making it easier for teachers to deliver material. Ideally, teachers need to develop teaching modules optimally according to the plans made. However, in reality many teachers do not understand the technique of compiling and developing teaching modules, especially in the independent learning curriculum.